«Vital context»: the novel «Singing Stones» of A. Zhaksylykov in the dialogue with traditions of classical Russian literature (Eurasian Journal of Philology Science and Education, 2016)
The work of art is considered in the article from the position of interliterary dialogue as a result of which the meanings in the text are enriched with «supercontent» – with value, aesthetic, ontological elements. As material for the analysis the author chose A. Zhaksylykov’s novel «The singing stones». The interpretation parameters – the chronotope and literary type – allow the researcher «to see» the multidimensionality of «artistic result».The process of intertextual dialogue as a result of which the literary text is enriched with universal valuable meanings, is considered in the article as «intertextual parallelism». The «axes» of art texts, developing in parallel, thus are subject to mutually reflection process. The similar reflection promotes identification of universal and ethnospecific «circles». On the material of the novel of A. Zhaksylykov «The singing stones» the author seeks to illustrate the existence of «the crossed parallels» and to designate their functions.
Keywords: interliterary dialogue; tradition; amplification; chronotope; literary type.